2022
DOI: 10.1126/sciadv.abq7433
|View full text |Cite
|
Sign up to set email alerts
|

Maximum strength and dislocation patterning in multi–principal element alloys

Abstract: Multi–principal element alloys (MPEAs) containing three or more components in high concentrations render a tunable chemical short-range order (SRO). Leveraging large-scale atomistic simulations, we probe the limit of Hall-Petch strengthening and deformation mechanisms in a model CrCoNi alloy and unravel chemical ordering effects. The presence of SRO appreciably increases the maximum strength and lowers the propensity for faulting and structure transformation, accompanied by intensification of planar slip and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This process requires additional work to overcome the energy barrier due to the change of alteration of the local chemical environments, which was confirmed by the experimental observation of nanotwins and very thin HCP phase in deformed HEAs [38,39]. Recent experimental and computational studies also reveal that LCO affects the slip mode of dislocation and deformation behaviors [3,40].…”
Section: Mechanical Properties and Deformation Behaviorsmentioning
confidence: 76%
“…This process requires additional work to overcome the energy barrier due to the change of alteration of the local chemical environments, which was confirmed by the experimental observation of nanotwins and very thin HCP phase in deformed HEAs [38,39]. Recent experimental and computational studies also reveal that LCO affects the slip mode of dislocation and deformation behaviors [3,40].…”
Section: Mechanical Properties and Deformation Behaviorsmentioning
confidence: 76%
“…The observation of rejuvenation in a quenched CrCoNi MEA after cyclic destruction of SRO offers critical insights into the impact of SRO on the mechanical performance of HEAs/MEAs, giving us a greater understanding of why certain HEAs/MEAs shows a combination of high strength and ductility. Previous MD simulations have shown that SRO in the CrCoNi MEA can lead to an increase in yield strength 13,38 . Furthermore, recent studies revealed that SRO can promote work hardening and thus enhance ductility 15 .…”
Section: Discussionmentioning
confidence: 97%
“…It can be observed that the density of the alloy presents a trend of increasing and the melting point is also on a trend of increasing with the increment of Cr content. From the predicted values, the density of the current alloys with varied Cr elements ranges between 6.25-6.32 g/cm 3 , and the melting point is in the range of 1247-1282 • C. Compared to the Inconel 718 superalloy with a density of 8.19 g/cm 3 , the density values of all the designed compositions of the alloys were less than 7 g/cm 3 , which is beneficial for lightweight superalloys with higher service temperatures. Thus, Cr 0.6 HEA has great potential to become an alternative material to meet the requirements of lightweight development in the aviation and aerospace industries.…”
Section: Constitutional-phase Formation and Microstructure Evolution ...mentioning
confidence: 99%
“…High-entropy alloys (HEAs) and multiprincipal element alloys have received considerable interest for community experts and have become a worldwide hot spot since Cantor and Yeh reported their first publication [1,2]. Cr-containing HEAs have exhibited promising potential when applied in high-temperature industrial fields as a result of their remarkable strength [3][4][5][6], favorable ductility [7][8][9], distinguished corrosion resistance [10][11][12], superior wear and oxidation resistance [13][14][15], and acceptable thermal stability [16,17].…”
Section: Introductionmentioning
confidence: 99%